2013
DOI: 10.17221/77/2012-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Forest visitors' opinion of recreational facilities and trails in forests in the Blaník Protected Landscape Area - a case study

Abstract: Currently, recreation is the most common use of protected areas and there are scarce data on the users and their opinion. The research was focused on visitors to the Blaník Protected Landscape Area (hereafter referred to as PLA), a well-known recreational area where data on visitors, important for PLA management, are missing. Therefore, the aim of the paper is find out: what kind of visitors comes to the study area; the type of forest trails and tourist facilities the visitors prefer. A questionnaire survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Contrarily, in the Czech Republic, forest visitors prefer the forest without additional facilities. Similar outcomes were found in the study of Drábková and Šišák ( 2013 ), where forest visitors predominantly demand maintained paths. Other studies from the urban green spaces have shown a higher preference for gravel surface and less maintained trails when compared to asphalt, but it also depends on the type and age of the respondents (Arnberger et al 2010 ; Reichhart and Arnberger 2010 ).…”
Section: Discussionsupporting
confidence: 86%
“…Contrarily, in the Czech Republic, forest visitors prefer the forest without additional facilities. Similar outcomes were found in the study of Drábková and Šišák ( 2013 ), where forest visitors predominantly demand maintained paths. Other studies from the urban green spaces have shown a higher preference for gravel surface and less maintained trails when compared to asphalt, but it also depends on the type and age of the respondents (Arnberger et al 2010 ; Reichhart and Arnberger 2010 ).…”
Section: Discussionsupporting
confidence: 86%
“…Besides the fact that the public is becoming more and more interested in conservation measures (Drábková, Šišák 2013), there is an urgent need to incorporate biodiversity-related information in policy-making, due to the depletion of natural resources. However, the number of indices that can be used for such purposes is strictly limited.…”
Section: Discussionmentioning
confidence: 99%
“…WOLF & CROFT (2014) quantified the strengths and spatial extent of tourism impacts along recreational tracks when examining the edge-effect on vegetation communities. The second approach presents motivations and focuses on the importance of trails in tourists' decisions when planning their trips (e.g., GOBSTER, 1995;JORGENSEN AT AL., 2002;FARÍAS TORBIDONI ET AL., 2005;DRÁBKOVÁ & ŠIŠÁK, 2013;KELLEY ET AL., 2016;KOEMLE & MORAWETZ, 2016). For instance, DRÁBKOVÁ & ŠIŠÁK (2013) investigated preferences for trail facilities and found out that maintained trails without equipment were the most preferred by tourists.…”
Section: Introductionmentioning
confidence: 99%